2010
DOI: 10.1073/pnas.0908191107
|View full text |Cite
|
Sign up to set email alerts
|

The Murray Springs Clovis site, Pleistocene extinction, and the question of extraterrestrial impact

Abstract: Some of the evidence for the recent hypothesis of an extraterrestrial impact that caused late Pleistocene megafaunal extinctions [Firestone et al. (2007) Proc Natl Acad Sci USA 104:16016–16021] was based upon samples collected at Murray Springs, a Clovis archaeological site in southeastern Arizona. Here we describe sampling and analyses of magnetic separates from within, above, and below the lower Younger Dryas boundary (LYDB) black mat at Murray Springs, as well as radiation measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 18 publications
3
45
2
Order By: Relevance
“…Bement et al (2014) concluded from sedimentological evidence that the peak ND accumulations in the YDB and younger strata did not result from changes in climate, deposition rates, lag deposits, or human site usage. Their results refute the hypothesis that the NDs simply resulted from cosmic influx that deposited them as a lag deposit at the YDB over an extended interval of time (Haynes et al 2010;Pinter et al 2011;Boslough et al 2012). Instead, Bement et al (2014) concluded the evidence is consistent only with cosmic-impact events.…”
Section: Introductioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Bement et al (2014) concluded from sedimentological evidence that the peak ND accumulations in the YDB and younger strata did not result from changes in climate, deposition rates, lag deposits, or human site usage. Their results refute the hypothesis that the NDs simply resulted from cosmic influx that deposited them as a lag deposit at the YDB over an extended interval of time (Haynes et al 2010;Pinter et al 2011;Boslough et al 2012). Instead, Bement et al (2014) concluded the evidence is consistent only with cosmic-impact events.…”
Section: Introductioncontrasting
confidence: 50%
“…In North America and the Middle East, Bunch et al (2012) identified YDB melt-glass that formed at high temperatures (1730Њ to 12200ЊC), as also reported by three independent groups, Mahaney et al (2010) in South America and Fayek et al (2012) and Wu et al (2013) in North America. This study focuses solely on nanodiamonds (NDs), and so, for independent discussions of other proxies, see Haynes et al (2010) and Paquay et al (2009), who found no evidence for the platinum-group elements iridium or osmium. Alternately, Wu et al (2013) found large YDB anomalies in osmium, as discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the published methodology adopted by Surovell et al, we suggest that their study may have suffered from this effect because size-sorting was not conducted. Finding a single spherule among 10,000 magnetic grains is such a tedious endeavor that some have claimed that any results may be highly subjective and therefore unreliable (14). In light of the above difficulties, we considered whether magnetic spherule counting is a quantitative science, or rather, a subjective art as suggested by Haynes et al (14).…”
Section: Resultsmentioning
confidence: 99%
“…Finding a single spherule among 10,000 magnetic grains is such a tedious endeavor that some have claimed that any results may be highly subjective and therefore unreliable (14). In light of the above difficulties, we considered whether magnetic spherule counting is a quantitative science, or rather, a subjective art as suggested by Haynes et al (14). Cognitive neuroscience might reveal whether limitations in human perception affect the ability of an operator to discriminate spherules among numerous non-spherulitic distractors.…”
Section: Resultsmentioning
confidence: 99%
“…18-21. Many of the impact markers reported in YD black mats have been widely discredited (22)(23)(24)(25)(26)(27) with the exception of the enigmatic nanodiamonds.…”
Section: Uring the End Of The Last Glacial Period In The Northernmentioning
confidence: 99%